Daya Saing Ekspor Cengkeh Indonesia Di Negara-Negara Tujuan Utama Dengan Pendekatan Revealed Symmetric Comparative Advantages (RSCA) Dan Export Product Dynamics (EPD) - Nursamsi, Nursamsi; Annisa, Khairun; Syahroni, Syahroni (LPPM Universitas Madako Tolitoli, 2025)
The potential for clove production excellence in Indonesia should be optimised to encourage an increase in export volume to international markets. The objective of this study is to analyse the competitive position of Indonesian clove exports to the global market as one of Indonesia's leading export commodities. The analysis used in this study is quantitative data analysis. The methods employed are the Revealed Symmetric Comparative Advantages (RSCA) analysis (Laursen, 2015) and Export Product Dynamics (EPD). Based on the analysis results, Indonesia's clove RSCA value is greater than zero. This indicates that cloves are one of Indonesia's competitive flagship products exported to the markets of India, Singapore, the United Arab Emirates, Saudi Arabia, and Vietnam compared to other export products. The growth of Indonesia's clove market share in major importing countries shows an ideal trend